Alternative Approach for Combination of Fingers in Underwater Acoustic Communication - Ji-Hong Son; Eun-Hye Jeon; Ki-Man Kim; Dong-Won Lee; Tae-Doo Park (International Journal of Distributed Sensor Networks)
An underwater acoustic communication channel is time varying and has multipath propagation with bottom and surface reflection. A rake receiver has time diversity effects in multipath propagation environments. We have to recognize the correct path for a rake receiver, as this affects communication performance in the underwater acoustic channel. In this paper, we propose a more reliable rake receiver based on BER (bit error rate) of training sequence duration. We conducted simulations and lake trials to evaluate the performance of the proposed method. When the channel coding technique was not applied, the uncoded BER performances of the proposed method, the conventional method, and the nonrake method in the lake trial were 0.016, 0.088, and 0.141, respectively.